2010
DOI: 10.1093/molbev/msq169
|View full text |Cite
|
Sign up to set email alerts
|

Dramatic Change in Function and Expression Pattern of a Gene Duplicated by Polyploidy Created a Paternal Effect Gene in the Brassicaceae

Abstract: New gene formation by polyploidy has been an ongoing process during the evolution of various eukaryotes that has contributed greatly to the large number of genes in their genomes. After duplication, some genes that are retained can acquire new functions or expression patterns, or subdivide their functions or expression patterns between duplicates. Here, we show that SHORT SUSPENSOR (SSP) and Brassinosteroid Kinase 1 (BSK1) are paralogs duplicated by a polyploidy event that occurred in the Brassicaceae family a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 46 publications
2
50
1
Order By: Relevance
“…Functional divergence of duplicated genes provides a source of evolutionary novelties in polyploids, including pseudogenization, neofunctionalization, and subfunctionalization (Force et al, 1999;Conant and Wolfe, 2008;Liu and Adams, 2010). Our study showed that an obvious subfunctionalization occurred in BnaC9.…”
Section: Discussionmentioning
confidence: 50%
“…Functional divergence of duplicated genes provides a source of evolutionary novelties in polyploids, including pseudogenization, neofunctionalization, and subfunctionalization (Force et al, 1999;Conant and Wolfe, 2008;Liu and Adams, 2010). Our study showed that an obvious subfunctionalization occurred in BnaC9.…”
Section: Discussionmentioning
confidence: 50%
“…Similar studies in maize (Waters et al 2011) and SSP mRNAs carried by Arabidopsis sperm are translated in zygotes and regulate the first asymmetric cell division that establishes apical (embryo) and basal (suspensor) cell fates (Bayer et al 2009). SSP acquired its current function sometime after a whole-genome duplication in an ancestor of the Brassicaceae (Liu & Adams 2010). mRNAs transcribed in male gametophytes and delivered to zygotes via sperm are subject to the same selective forces as PEGs transcribed in embryos after fertilization.…”
Section: Genomic Imprinting In Embryosmentioning
confidence: 63%
“…It is tempting to speculate that in L. papillosum, the two LepaDOG1a and LepaDOG1c proteins provide functional roles in dormancy regulation that are fulfilled by different splice variants of the single AtDOG1 gene (Bentsink et al, 2006;Nakabayashi et al, 2012) in the shrunken genome of Arabidopsis, which is characterized by extensive gene loss (Thomas et al, 2006;Oyama et al, 2008). Furthermore, polyploidization can form the basis for neofunctionalization or subfunctionalization of multiplied and retained genes (homeologs; Erdmann et al, 2010;Liu and Adams, 2010;Franzke et al, 2011), providing a mechanism for potentially diversified or more complex functions of the individual LepaDOG1 proteins in a putatively conserved dormancy mechanism. As outlined above, we propose that L. papillosum evolved by autopolyploidization or allopolyploidization from the very closely related L. oxytrichum (or its progenitor).…”
Section: Discussion Spatiotemporal Maturation Patterns In L Papillosmentioning
confidence: 99%